Trust and violence : an essay on a modern relationship - Reemtsma, Jan Philipp (Princeton University Press, 2012)
The limiting of violence through state powers is one of the central projects of the modern age. Why then have recent centuries been so bloody? In Trust and Violence, acclaimed German intellectual and public figure Jan Philipp Reemtsma demonstrates that the aim of decreasing and deterring violence has gone hand in hand with the misleading idea that violence is abnormal and beyond comprehension. We would be far better off, Reemtsma argues, if we acknowledged the disturbing fact that violence is normal. At the same time, Reemtsma contends that violence cannot be fully understood without delving into the concept of trust.